PERLINDUNGAN HUKUM TERHADAP PELAKU TINDAK PIDANA PENCUCIAN UANG PASIF YANG MEMILIKI ITIKAD BAIK UNTUK MEWUJUDKAN KEPASTIAN HUKUM - Mochamad Luthfi Zulfikar; Kristiawanto Kristiawanto; Marsudin Nainggolan (SINERGI : Jurnal Riset Ilmiah, 2026)
This study aims to analyze the legal regulation of passive money laundering perpetrators who have good intentions based on positive law in Indonesia and analyze the form of legal protection for passive money laundering perpetrators who have good intentions to realize legal certainty. The issues raised focus on how to regulate passive money laundering perpetrators who have good intentions based on positive law in Indonesia and what form of legal protection for passive money laundering perpetrators who have good intentions to realize legal certainty. The research method used is normative legal research with a statute approach, a conceptual approach, a case approach, and a comparative approach. Data sources are obtained from primary legal materials in the form of the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945), the Criminal Code (KUHP), Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering Crimes, Regulation of the Supreme Court of the Republic of Indonesia Number 1 of 2013 concerning Procedures for Settling Applications for Handling Assets in Money Laundering Crimes or Other Crimes, Government regulations or other implementing regulations. The research findings implementation of passive money laundering perpetrators who have good intentions has adopted a broad approach to encompassing passive perpetrators to enhance the effectiveness of crime eradication. However, this expansion still leaves legal issues, particularly regarding the unclear parameters of the phrase "knowingly or reasonably suspected" and the lack of explicit regulation of the concept of good faith, which has the potential to create legal uncertainty and the risk of criminalization of innocent parties. On the other hand, legal protection for passive perpetrators acting in good faith is essentially available through various mechanisms, such as the right to object, judicial procedures, Supreme Court guidelines, and whistleblower immunity. However, these regulations still need to be refined to achieve a more optimal balance between the effectiveness of money laundering and guarantees of justice and legal certainty. This research concludes that legal protection for passive perpetrators acting in good faith is essentially available through various mechanisms, such as the right to object, judicial procedures, Supreme Court guidelines, and whistleblower immunity